Risk factors for 90-day mortality after pancreaticoduodenectomy - Yur, Mesut; Aygen, Erhan; Ilhan, Yavuz Selim; Kirkil, Cuneyt; Yilmaz, Serkan; Akbas, Ahmet (Bmc, 2025)
Background Pancreaticoduodenectomy (PD) is a key surgical procedure for periampullary cancer, but it has a concerning postoperative mortality rate. This study evaluates the risk factors influencing 90-day mortality after PD in periampullary cancer patients. Methods Between January 2010 and August 2022, 105 eligible patients with PD were included in the study. Demographic, pathological, and laboratory data were collected for this research. The study also included the MELD-Na score, the age-adjusted Charlson Comorbidity Index (ACCI), and the neutrophil-lymphocyte ratio (NLR). The patients were divided into two groups: those who experienced 90-day mortality (17 patients in group I) and those who were discharged (88 patients in group II). Kaplan-Meier analysis and Cox proportional hazards model were utilized to identify the prognostic factors associated with 90-day mortality. Results In the univariate analysis, age, sex, albumin levels, NLR, MELD-Na scores, and ACCI were significantly associated with 90-day postoperative mortality (p<0.05). In multivariate analysis, the MELD-Na score at the admission (HR: 10.75; 95% CI: [2.82-61.30]; p = 0.001), ACCI (HR: 9.30; 95% CI: [2.30-46.05]; p < 0.001), and NLR (HR: 7.81; 95% CI: [1.98-48.38]; p = 0.005) were independent risk factors for postoperative 90-day mortality. Conclusions Although several factors affect 90-day postoperative mortality after pancreaticoduodenectomy, the MELD-Na score, ACCI, and NLR are independent risk factors. Assessing patients in the risk group separately by a multidisciplinary team may reduce mortality.
Keywords: Pancreaticoduodenectomy; Mortality; MELD-Na; Risk factors